Eat My Dust Early Women Motorists - Clarsen, Georgine (Johns Hopkins University Press, 2008)
The history of the automobile would be incomplete without considering the influence of the car on the lives and careers of women in the earliest decades of the twentieth century. Illuminating the relationship between women and cars with case studies from across the globe, Eat My Dust challenges the received wisdom that men embraced automobile technology more naturally than did women.Georgine Clarsen highlights the personal stories of women from the United States, Britain, Australia, and colonial Africa from the early days of motoring until 1930. She notes the different ways in which these women embraced automobile technology in their national and cultural context. As mechanics and taxi drivers-like Australian Alice Anderson and Brit Sheila O'Neil-and long-distance adventurers and political activists-like South Africans Margaret Belcher and Ellen Budgell and American suffragist Sara Bard Field-women sought to define the technology in their own terms and according to their own needs. They challenged traditional notions of femininity through their love of cars and proved they were articulate, confident, and mechanically savvy motorists in their own right.More than new chapters in automobile history, these stories locate women motorists within twentieth-century debates about class, gender, sexuality, race, and nation.